Designing A Spice Storage Area With Additional Compartment Features to Support The Needs of Housewives - Kurnia, Adzdzaniyah Brenda; Yunidar, Dandi; Putri, Sheila Andita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
East Javanese cuisine is a type of traditional cuisine originating from East Java. East Java cuisine has a variety of flavors, from savory to sweet and spicy. Spice storage is needed for kitchen needs in cooking activities. This design aims to produce a prototype of the spice storage concept to facilitate cooking activities for East Javanese cuisine. The goal was found because the spice storage has no special product for storing spices in East Java cuisine and this problem occurs, so a spice storage is designed with a home kitchen. The design of spice storage is designed with additional features as needed such as sachet holders and bottle holders. The design method is made with the UCD (User Centered Design) method with this method carried out thoroughly starting from the target audience to the product test stage and solutions to users based on data that has been collected. Previous data was taken from interviews, observations, and found data from journals and books. Analyze the results of observations and interviews that have been conducted. In the design process from the ideation stage to the product finishing stage. The results and data analysis, obtained that the spice storage case study of East Java cuisine can support the needs of housewives.